FAKTOR – FAKTOR YANG MEMPENGARUHI BEBAN KERJA MENTALPADA GURU SEKOLAH DASARDI KELURAHAN BAJUBANG - Atika Atika; Rara Marisdayana; Cici Wuni (Sekolah Tinggi Pariwisata Mataram, 2023)
Physiologically, mental activity is seen as a type of light work so that the caloric requirement for mental activity is also lower. Even though morally and responsibly, mental activity is heavier than physical activity because it involves brain work (white-collar) rather than muscle work (blue-collar). This research is a quantitative research with a descriptive research design with a cross-sectional research type. The factors studied were work atmosphere, psychological work environment, and psychological factors. The population in this study was all elementary school teachers in the Bajubang sub-district, totaling 61 people. The research sample was 58 people. Data collection in this study was carried out using a questionnaire. Data were analyzed by means of univariate and bivariate with chi-square. The results showed that there was a significant relationship between the work atmosphere p-value (0.023), the psychological work environment p-value (0.030), the psychological factors p-value (0.027) and the mental workload of elementary school teachers in the Bajubang Village in 2021. There is a significant relationship between work atmosphere, work environment and psychological factors on mental workload for elementary school teachers in the Bajubang Subdistrict in 2021. It is recommended that teachers be more creative in creating a good working atmosphere such as ensuring the lighting of the work space, or decorating the work space so that it looks more colorful, make special events with colleagues and create a lively atmosphere while teaching so it doesn't cause boredom while working.